2021
DOI: 10.3762/bjoc.17.160
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective PCCP Brønsted acid-catalyzed aminalization of aldehydes

Abstract: Here we present an enantioselective aminalization of aldehydes catalyzed by Brønsted acids based on pentacarboxycyclopentadienes (PCCPs). The cyclization reaction using readily available anthranilamides as building blocks provides access to valuable 2,3-dihydroquinazolinones containing one stereogenic carbon center with good enantioselectivity (ee up to 80%) and excellent yields (up to 97%).

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Surprisingly, the utilization of Rose Bengal or Eosin Y organic dyes, in the lieu of 4CzIPN, delivered 3aa in diminished yields (Table 1, entries 2-3). In the survey of sacrificial oxidant, the employment of (NH4)2S2O8 or NFSI resulted in 3aa in slightly reduced yields, whereas ditert-butyl peroxide (DTBP) remains completely ineffective (Table 1, entries [4][5][6]. Altering the solvent from DMF to NMP (NMP = N-methyl-2-pyrrolidone) or DCE (DCE = 1,2dichloroethane) led to the drastic change in the yields of 3aa (Table 1, entries 7-8).…”
Section: Scheme 1 An Overview Of Csp 2 -H Alkylation Of N-heteroarene...mentioning
confidence: 99%
See 1 more Smart Citation
“…Surprisingly, the utilization of Rose Bengal or Eosin Y organic dyes, in the lieu of 4CzIPN, delivered 3aa in diminished yields (Table 1, entries 2-3). In the survey of sacrificial oxidant, the employment of (NH4)2S2O8 or NFSI resulted in 3aa in slightly reduced yields, whereas ditert-butyl peroxide (DTBP) remains completely ineffective (Table 1, entries [4][5][6]. Altering the solvent from DMF to NMP (NMP = N-methyl-2-pyrrolidone) or DCE (DCE = 1,2dichloroethane) led to the drastic change in the yields of 3aa (Table 1, entries 7-8).…”
Section: Scheme 1 An Overview Of Csp 2 -H Alkylation Of N-heteroarene...mentioning
confidence: 99%
“…4 Particularly, encouraged by the beneficial effect of enhanced Csp 3 fraction in the prodrugs or lead structures in drug discovery, 5 recently, selective alkylation of N-heteroarenes has perceived the prominence for building up structural complexity in the molecular skeletons. 6 In this regard, catalytic C-H alkylation of electron-deficient N-heteroarenes -Minisci-type Reaction − is epitomized for direct installation of Csp 3 fragment to Nheteroaryl core. 6 While the classic Minisci reaction of Nheteroarenes with aliphatic carboxylic acids has posed limitations under relatively harsh conditions, 7 the monumental encroachment of visible light photocatalysis 8 has enabled the broadening of the territory of alkyl radical precursors, such as alkyl halides, 9a-c alkylborates 9d,e or alkylsilicates, 9f alcohols, 9g-i aldehydes 9j,k or aldehyde-derived dihydropyridines (DHPs), 9l carboxylic acids 9m-o or their redox-active esters, 9p-r aminederived pyridinium salts, 9s and even native C-H bonds, 9t-y among others 9z for the alkylation of such heteroarenes (Scheme 1).…”
mentioning
confidence: 99%
“…Pentacarboxycyclopentadienes are a unique type of Brønsted acid catalyst that expanded the range of available acidities as well as molecular arrangements in acid-catalyzed reactions. Veselý and co-workers demonstrated that these catalysts are effective in the enantioselective aminalization of aldehydes with anthranilamides [ 24 ]. To explore new possibilities in combination of covalent and noncovalent activation, our group designed and synthesized N -sulfinylpyrrolidine-containing ureas and thioureas and applied them in Michael additions of aldehydes to heterocycle containing nitroalkenes [ 25 ].…”
mentioning
confidence: 99%